Circular economy - Cofie, Olufunke O.; Nikiema, Josiane (2021)
The Sanitation and Wastewater Atlas of Africa provides a comprehensive assessment of the continent’s sanitation and wastewater management landscape, revealing substantial infrastructural and governance deficiencies. Access to improved sanitation remains uneven, with coverage exceeding 90% in North Africa but falling below 30% in sub-Saharan regions. Most populations rely on on-site sanitation systems, such as pit latrines and septic tanks, while less than 20% are connected to centralized sewerage networks. The discharge of untreated wastewater estimated to exceed 90% is a significant source of pollution in freshwater and marine ecosystems, contributing to nutrient loading, eutrophication, and increased incidence of waterborne diseases. Key wastewater streams include municipal, industrial, agricultural, hospital, and stormwater runoff. These sources collectively compromise ecosystem functions and human health, particularly in urban and peri-urban areas. Despite recognition of the potential benefits of circular economy approaches such as nutrient recovery, water reuse in agriculture, and biogas generation adoption remains limited due to institutional fragmentation, inadequate funding, and limited technical capacity. To address these challenges, the Atlas advocates for integrated policy frameworks, enforcement of effluent discharge standards, investment in decentralized treatment systems, and improved data monitoring. Advancing safely managed sanitation services is essential to meeting Sustainable Development Goal 6 and realizing Africa’s Agenda 2063 objectives.